KEMAMPUAN LITERASI BACA TULIS NUMERASI SERTA BUDAYA DAN KEWARGAAN SISWA MI DI KOTA BANJARMASIN - Khairunnisa Khairunnisa; Raihanatul Jannah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This study aims to find out the ability of literacy, numeracy, citizenship and cultural literacy of Islamic elementary school students in Banjarmasin. The sample in this study amounted to 106 students of class V Madrasah Ibtidaiyah Banjarmasin which was determined by purposive sampling. The technique of collecting data is objective test. Data processing through editing, classification, scoring, and tabulating. Data were analysed by quantitative descriptive method with inductive decision-making techniques. Student ability in literacy is still sufficient with an average value of 56.03, while numeracy literacy is still lacking with an average value of 34.84. The citizenship cultural literacy also showed the same results as literacy, which was on the sufficient criteria with an average value of 54.19. The lacking in numeracy is caused by student ability to operate addition, multiplication and division that is not yet good. Meanwhile, the respondents did not understand the content of the text. In addition, the respondent’s achievement is also influent by the format or type of question. Students are not used to doing test with the AKM format.